Analisa dan Perancangan Sistem Informasi Akuntansi Penjualan (Point of Sales) pada Koperasi Karyawan Bina Nusantara - Udiono, Tangkas (Bina Nusantara University, 2010)
The diversity of the sales transaction and the high frequency of sales in retail stores now requires store owners to be gave the best service is speed and accuracy of the data presented remains the main choice, not to mention the number of items owned, couse enormous amounts sometimes cause difficulties to provide a unique characteristic feature of each item. Cash register machines are not able to gradually overcome the kinds of sales that various kinds, and happens due to the emergence of the sales transaction itself such as the purchase or cancel the presentation of consolidated sales. So the point of sales aims to cover all the deficiencies that existed at the machine registers cash